Analysis of Technology Acceptance Model Method To Predict A Person's Interest In The Acceptance of A Technology : A Literature Review - Tito Prabowo; Wing Wahyu Winarno; Sudarmawan Sudarmawan (Universitas Medan Area, 2020)
The Technology Acceptance Model (TAM) is a model used by researchers to predict and analyse factors that influence a person's interest in a technology. The purpose of this literature review is to find out how the interests of users of an information system are investigated. This literature review is based on a thorough review of the research and a descriptive discussion based on previous studies that investigate the acceptance of an information system. Previous researchers have used good research methods and research steps, so the results of the study can also give an idea of how user interests strongly influence the usefulness and actual actions when using an information system. The results of a systematic review show that the TAM method for predicting an individual's interest in accepting an information technology relationship between constructs used is a determinant that can measure interest in user behavior and also a determinant that can predict and explain interest in user behavior.Keywords: Technology Acceptance Model, Behavior Interests, User Behavior.